2021
DOI: 10.1038/s41467-021-24328-w
|View full text |Cite
|
Sign up to set email alerts
|

Four chromosome scale genomes and a pan-genome annotation to accelerate pecan tree breeding

Abstract: Genome-enabled biotechnologies have the potential to accelerate breeding efforts in long-lived perennial crop species. Despite the transformative potential of molecular tools in pecan and other outcrossing tree species, highly heterozygous genomes, significant presence–absence gene content variation, and histories of interspecific hybridization have constrained breeding efforts. To overcome these challenges, here, we present diploid genome assemblies and annotations of four outbred pecan genotypes, including a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 87 publications
(107 reference statements)
0
49
0
Order By: Relevance
“…With recent advances in long-read sequencing and assembly technologies, such structural variation is evident in chromosomal haplotype assemblies for polyploid and highly heterozygous genomes (e.g., refs. 32 , 44 , 46 ). Until recently, such high-quality genomes were primarily produced for inbred crop and genetic model species, but they are increasingly emerging for plant species outside these criteria (e.g., Lindenbergia , Acorus , Joinvillea , and Pharus ; https://phytozome-next.jgi.doe.gov/ogg/ ).…”
Section: What Do We Mean By a “Genome” In Plants? Why Are High-quality Genomes Needed?mentioning
confidence: 99%
“…With recent advances in long-read sequencing and assembly technologies, such structural variation is evident in chromosomal haplotype assemblies for polyploid and highly heterozygous genomes (e.g., refs. 32 , 44 , 46 ). Until recently, such high-quality genomes were primarily produced for inbred crop and genetic model species, but they are increasingly emerging for plant species outside these criteria (e.g., Lindenbergia , Acorus , Joinvillea , and Pharus ; https://phytozome-next.jgi.doe.gov/ogg/ ).…”
Section: What Do We Mean By a “Genome” In Plants? Why Are High-quality Genomes Needed?mentioning
confidence: 99%
“…The USDA-ARS Pecan Breeding program has been using these 14 nuclear and 3 plastid SSR markers to identify cultivars, hybrids, and unknown varieties. Recently, three of these SSR markers were used to identify F 1 progeny in a cross of "Lakota" × 87MX3-2.11, which was used for candidate gene identification [44]. Existing profiles from verified inventories will be useful in establishing additional methods of molecular verification [18].…”
Section: Discussionmentioning
confidence: 99%
“…Additional microsatellite markers should be selected for their distribution across all chromosomes and high nucleotide repeat numbers (tri and tetra). Next-generation sequencing technology provides a more efficient tool to quickly profile tree species with a greater resolution of interspecific hybridity, especially when their markers (SNPs) are aligned to an available chromosome-scale genome sequence [27,44]. However, SSR markers still have great utility for plant breeding programs and researchers who need markers that have high reproducibility, transferability between species, and platform independence.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 32 SPL genes were identified in the pecan genome, which was two more SPL genes than what was found in previous studies. We also identified the SPL gene family of pecan from the newly released genome ( https://phytozome-next.jgi.doe.gov/info/CillinoinensisPawnee_v1_1 ) ( Lovell et al, 2021 ). The number of SPL gene family members was found to be the same in the two versions of the pecan genome ( Table S8 ).…”
Section: Discussionmentioning
confidence: 99%